Melancholy and the body in the eighteenth century: the example of Samuel Johnson (ACME, 2017)
Samuel Johnson (1709-1784), the great lexicographer and essayist, suffered from melancholy all his life. He believed that the disorder was congenital and that it afflicted his mind. To some degree, he saw the problem as arising in his abnormally large and partially disabled body. Locating the source of melancholy in his body, gave Johnson a way to deal with it, and it partially relieved him of the guilt and shame he felt concerning the disease. Johnson’s greatest fear concerning his condition was that it touched not only his mind but also his soul. In the form of scruples and spiritual torpor, melancholy weighed Johnson down and stimulated his fears of death and damnation. As a physical body, Johnson was perhaps deformed, but he was courageous. No physical danger frightened him, but he trembled for the life of his soul, and his melancholy, even if it was psycho-somatic (avant la lettre), was his greatest threat.